1997
DOI: 10.1007/bf02291530
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active polysaccharides from medicinal plants of the Far East

Abstract: Plant polysaccharides are attracting ever-increasing attention as an important class of biopolymers possessing a broad spectrum of biological action. Antitumoral, immunostimulating, hypoglycemic, anticomplement, antiinflammatory, anticoagulant, and other types of activities have been found in these compounds [1][2][3][4].The rich and unique flora of the Far East may serve as a source of biologically active polysaccharides. To select the most interesting and promising sources, we have made a comparative study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…G. littoralis roots (Radix Glehniae) are rich in polysaccharides, phospholipids, coumarins, coumarin glycosides and polyacetylenes ( Tomshich et al, 1997 ; Yuan et al, 2002 ). G. littoralis grows naturally in coastal regions, and is considered a high-quality medicinal herb in traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…G. littoralis roots (Radix Glehniae) are rich in polysaccharides, phospholipids, coumarins, coumarin glycosides and polyacetylenes ( Tomshich et al, 1997 ; Yuan et al, 2002 ). G. littoralis grows naturally in coastal regions, and is considered a high-quality medicinal herb in traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…They have been used as a functional food and as a well-known Chinese traditional medicine with health effects on removing dryness, promoting fluid secretion, and quenching thirst ( 1 ). It has been reported that a variety of chemical components of Polygonatum species possess different biological properties, such as antioxidant, anti-inflammatory, anti-diabetic, antitumor, and immunomodulatory activities ( 2 ). Liu et al reported that the water extract of Polygonatum sibiricum was capable of reducing blood glucose and lipid levels, regulating and enhancing the immune system, and fighting aging ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the polysaccharides from Irpex lacteus have been seldom reported. Many active compounds have been identified in Polygonatum odoratum such as mucous polysaccharides and homoisoflavanones (Tomshich et al 1997), azetidine-2-carboxylic acid (Baek et al 2012;Kim et al 2006), saponin (Deng et al 2012), andsteroidal compounds (Sugiyama et al 1984). Among them, polysaccharides are abundant in Polygonatum odoratum and considered as one of the most important bioactive components with antitumor, antidiabetic, and antioxidant functions.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Extraction of polysaccharides from Polygonatum odoratum is an important approach to further research or scale application. Tomshich et al (1997) reported extraction and purification of polysaccharides from ten medicinal plants including Polygonatum odoratum, and several reports were documented on extraction and bioactivities of polysaccharides from this species in recent years (Baek et al 2012). …”
Section: Biological Activitiesmentioning
confidence: 99%